Pengembangan LKPD Motorik Anak Berbasis Permainan Tradisional untuk Kelas 2 Sekolah Dasar - Catur Prasetyo Catur Prasetyo Irdiyanuar; Yudha Febrianta (JSH: Journal of Sport and Health, 2025)
This study aims to develop traditional game-based Children's Motor Activity Sheets (CMAS) using the ADDIE development model for 34 second grade students of SD Negeri 2 Bojanegara. This research instrument includes a validity test by experts, teacher and student response questionnaires, as well as pretest and postets questionnaires. Data analysis used averages and effectiveness tests using the Wilcoxon sign rank statistical test and paired sample t test on three traditional games, namely cranklek, gopak sodor, and sack racing. The results showed that the traditional game-based children's motor LKPD was valid with an average expert validity score of 76%. Teacher and student responses were very positive with an average assessment score of 96% and 87% respectively. The effectiveness test on the three traditional games showed a statistically significant increase in students' gross motor skills (sig. 0.00 <0.05). This LKPD is proven to be effective and relevant as an innovative learning media that is fun and supports the preservation of local culture in the elementary school environment. The implication of this research is that the use of traditional game-based LKPD can be an alternative learning media that is holistic and supports early childhood motor development in Indonesia .